PERSEPSI GURU TENTANG PROGRAM KESEHATAN JIWA BERBASIS SEKOLAH (PKJ-BS) - Wardiyah Daulay; Sri Eka Wahyuni; Mahnum Lailan Nasution (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Mental health services for school-age children are very helpful in preventing more serious problems. Mental health problems that are mild in nature can be handled by the teacher at school or in collaboration between the teacher and the child's parents. To create a conducive climate, it is necessary to develop a mental health program in schools to be able to facilitate school-age children to achieve their developmental tasks. This study used an action research design. The implementation procedure consists of four stages, namely reconnection, planning, acting and reflecting. Research respondents were all 12 teachers in SD Negeri 060891. At the reconnaissance stage of qualitative analysis, the data were recorded and documented in the form of a transcript which then determined the appropriate theme. The stages of Reconnaissance were carried out by means of FGD (Focus Group Discussion) on research on the Development of School-Based Mental Health Programs (PKJ-BS) at SD Negeri 060891 Medan resulting in 6 themes, namely: 1) teachers' knowledge of mental health for school age children, 2) mental health problems in school-age children, 3) teacher's handling of mental health problems for school-age children, 4) mental health education for school-age children, 5) parental involvement and 6) efforts made by schools to improve mental health for school-age children. It is recommended that the health and education offices work together in developing the mental health of school-age children in order to improve student achievement